Combining high pressure homogenization with free nitrous acid pretreatment to improve anaerobic digestion of sewage sludge. (15th September 2022) - Nabi, Mohammad; Gao, Dawen; Liang, Jinsong; Cai, Yajing; Zhang, Panyue
Abstract: Single pretreatment of sewage sludge, either physical, chemical or biological, has its own drawbacks in term of poor sanitization, energy intensity and high operational and capital cost. To tackle these drawbacks, combined high pressure homogenization (HPH) and free nitrous acid (FNA) pretreatment for sludge solubilization and further biodegradation in anaerobic digestion was investigated. Synergistic effect of combined HPH (40 MPa) and FNA (2.49 mg/L) pretreatment (HPH-FNA) for improving anaerobic digestion was evaluated, and its effect on archaeal and bacterial community structure was analyzed. Compared with single HPH and FNA pretreatments, HPH-FNA pretreatment efficiently solubilized wasted activated sludge (WAS), subsequently improved anaerobic digestion. Cumulative biogas production from sewage sludge pretreated with HPH-FNA was 154%, 108% and 284% more than that with single pretreatment of FNA, HPH and raw sludge, respectively. In addition, volumetric biogas production of combined pretreatment system (815 ml) was more than the sum from single pretreatment (710 ml). Methane content in biogas for raw sludge, FNA, HPH and HPH-FNA pretreated sludge was 45%, 51%, 55% and 65%, respectively. Illumina MiSeq sequencing analysis revealed that HPH-FNA pretreatment promoted bacterial growth of phyla Bacteroidetes, Firmicutes and Synergistetes and archaeal genera Methanospirillum and Methanosaeta . Overall, combined HPH-FNA pretreatment of sewage sludge, prior to anaerobic digestion, is an environmentally-friendly and potentially economic technology. Highlights: Sludge pretreatment by high pressure homogenization-free nitrous acid (HPH-FNA). HPH-FNA pretreatment efficiently disintegrated sewage sludge. 15% more biogas was produced by HPH-FNA pretreatment than sum of single HPH and FNA. Methane content in biogas increased with the increase of DDCOD (R 2  = 0.9994). Increase in abundance of anaerobes reflect positive effect of HPH-FNA pretreatment.